„Az igaz ember hitből él” (Róma 1,17) – a hit, mint a református önértelmezés fő alkotóeleme - PÜSÖK, Sarolta (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2017)
The Just Shall Live by Faith. (Romans 1,17) – Faith, as the Main Factor of the Reformed Identity. The topic is actual on one hand because of the 500th anniversary of Reformation, on the other hand because of the identity crisis particular to transition periods. From time to time we should rethink which factors define the reformed identity. From these theological concepts forming the identity this study focuses on faith. Based on the reformed definition of faith it involves intellect, emotion and will, so faith has cognitive, emotive and volitive aspects. The last one involves confession and living the faith. Confession is much more than a testimony in words, the works of love and a lifestyle reflecting the confessed values also belong to it. In the protestant view acts of kindness do not precede, earn salvation, they follow it, as acts of thankfulness. There is healthy spirituality only if the three aspects of the faith are in balance. The last ideas refer to the development of faith in all of the three directions, there are given some examples from church history.